Towards Printed Organic Light‐Emitting Devices: A Solution‐Stable, Highly Soluble CuI–NHetPHOS1. Issue 46 (6th October 2016) - Wallesch, Manuela; Verma, Anand; Fléchon, Charlotte; Flügge, Harald; Zink, Daniel M.; Seifermann, Stefan M.; Navarro, José M.; Vitova, Tonya; Göttlicher, Jörg; Steininger, Ralph; Weinhardt, Lothar; Zimmer, Manuel; et al.
Abstract: The development of iridium‐free, yet efficient emitters with thermally activated delayed fluorescence (TADF) was an important step towards mass production of organic light‐emitting diodes (OLEDs). Progress is currently impeded by the low solubility and low chemical stability of the materials. Herein, we present a Cu I ‐based TADF emitter that is sufficiently chemically stable under ambient conditions and can be processed by printing techniques. The solubility is drastically enhanced (to 100 g L −1 ) in relevant printing solvents. The integrity of the complex is preserved in solution, as was demonstrated by X‐ray absorption spectroscopy and other techniques. In addition, it was found that the optoelectronic properties are not affected even when partly processing under ambient conditions. As a highlight, we present a TADF‐based OLED device that reached an efficiency of 11±2 % external quantum efficiency (EQE). Abstract : A new NHetPHOS–Cu I emitter was synthesized and characterized. With synchrotron‐based X‐ray absorption spectroscopy, proof is provided that changes of the photophysics in solution compared with solid‐state results are not a result of dissociation. The evidence that the material can be processed in the presence of ambient air with inkjet‐printing, even in the absence of a host material, is presented. In a refined device, efficiency values of more than 11 % EQE were obtained (see scheme).